2012
DOI: 10.15517/rbt.v60i4.2068
|View full text |Cite
|
Sign up to set email alerts
|

Leaf damage and density-dependent effects on six Inga species in a neotropical forest

Abstract: Many models have been proposed to explain the possible role of pests in the coexistence of a high diversity of plant species in tropical forests. Prominent among them is the Janzen-Connell model. This model suggests that specialized herbivores and pathogens limit tree recruitment as a function of their density or proximity to conspecifics. A large number of studies have tested the predictions of this model with respect to patterns of recruitment and mortality at different life stages, yet only a few have direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…For example, the Janzen‐Connell hypothesis posits that herbivores may exert density‐dependent effects on plant mortality by feeding preferentially on seeds or plants occurring in dense patches of conspecifics, causing mortality and thereby opening space on the forest floor for the recruitment of additional species (Connell, 1971; Janzen, 1970). This hypothesis has inspired years of study (reviewed by Carson et al, 2008; Comita et al, 2014; Song et al, 2021), but not all data support its predictions (Hyatt et al, 2003; Brenes‐Arguedas, 2012; Song et al, 2021). This may be because, as Janzen himself noted, herbivores do not perceive their would‐be host plants as taxonomic units but rather as chemical entities that may be nutritious or deterrent, depending on their chemistry (Janzen, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Janzen‐Connell hypothesis posits that herbivores may exert density‐dependent effects on plant mortality by feeding preferentially on seeds or plants occurring in dense patches of conspecifics, causing mortality and thereby opening space on the forest floor for the recruitment of additional species (Connell, 1971; Janzen, 1970). This hypothesis has inspired years of study (reviewed by Carson et al, 2008; Comita et al, 2014; Song et al, 2021), but not all data support its predictions (Hyatt et al, 2003; Brenes‐Arguedas, 2012; Song et al, 2021). This may be because, as Janzen himself noted, herbivores do not perceive their would‐be host plants as taxonomic units but rather as chemical entities that may be nutritious or deterrent, depending on their chemistry (Janzen, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Although not directly comparable, this finding contrasts with results from another study, which found that weevil attack rates on acorns of Q. ilex depended on CPD (Bogdziewicz et al, 2018). Further work manipulating seedling densities and separating damage by different insect species is needed for a more detailed and rigorous investigation of herbivore density‐dependent responses in this system (Brenes‐Arguedas, 2012; Abdala‐Roberts et al, 2017). Including other sympatric tree species with broad distributions and manipulating species relative frequencies would also be of high value to describe community‐level patterns and separate intra‐ from interspecific associational effects (sensu Kim and Underwood, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have found that, contrary to predictions, adult conspecifics have stronger effects on seedling mortality in dry (Palamanui, Hawaii, 835 mm of annual rainfall) compared to wet forests (Inman-Narahari et al . 2016), but in certain cases, damage (herbivory) is not correlated with density in tropical rain forests (Brenes-Arguedas 2012). If negative density-dependence increases with rainfall (Comita et al .…”
Section: Discussionmentioning
confidence: 99%